Collaborative Education Issues in Indonesia - Syamsi, Ibnu; Noormiyanto, Faiz (Angstrom Centre of Education, 2024)
Education issues Collaboration in Indonesia includes lack, lack of connections between teachers, professionals, schools, parents and social stigma towards students with special needs. So from improved teacher training, increased understanding of parents, schools, and campaigns to change the perception of society. The importance of educational policies that support collaborative inclusion. Through the cooperation of governments, educational institutions, experts/professionals, teachers, parents, and the community, collaborative education can be realized. The vision of inclusion is to provide quality education to all students, without discrimination. This collaboration enables every student, including those with special needs, to reach their full potential in an inclusive and supportive environment.